International economics - Carbaugh, Robert J. (Cengage Learning, 2015)
INTERNATIONAL ECONOMICS vividly demonstrates the relevance of theory to real-world economic issues and policy questions. Discussions are presented both verbally and graphically, making the text highly accessible even for students with little economics background, and a flexible format makes the text suitable for a wide range of course structures and subjects.